Late angiographic evaluation of radial artery grafts used in surgical myocardial revascularization - Siderval Ferreira Alves (Brazilian Journal of Cardiovascular Surgery, 2003)
OBJECTIVE: To evaluate the late patency of the radial artery used as a conduit in coronary artery bypass grafting through a selective catheterization. METHOD:A group of 109 patients operated on for coronary artery bypass grafting used radial artery as grafts, from September 1995 to October 1996, were re-studied in the immediate post-operative period. Among these patients, 91 (83.5%) were contacted either by phone or through outpatient follow-ups, and 34 underwent a late angiographic study. Twenty-two patients were male (65%). The average age of the patients was 57.4 years old (37-70). The average time of the restudy was of 51.2 months (41-63). Thirty-eight distal anastomoses were performed using the radial artery, with an average of 1.12 distal anastomoses per patient. The analysis of these data is the basis for the present study. RESULTS: The radial artery was patent in 30 patients (34 distal anastomoses - 89.5%), and had a lesion in only one patient along with the proximal anastomosis in the aorta. Out of the four patients who presented total graft obstruction, two were male. We observed inadequate indications in two patients, and no justifiable occlusions in the others. From the 91 re-studied patients in the immediate post-operative period, there was late mortality in 6 patients (6.6%), one adenocarcinoma of the lung, and the others by cardiac causes. The only patient who presented a lesion at the radial artery underwent angioplasty with a stent implantation and had a satisfactory outcome. CONCLUSIONS: The radial artery, used as a conduit for coronary artery bypass grafting, shows satisfactory angiographic aspects and also a satisfactory patency, similar to those of the left internal thoracic artery, when evaluated in this time of follow-up.